Pengaruh Atribut Produk Terhadap Keputusan Pembelian Ladaku Merica Bubuk Di Kota Surakarta - Muhamad Rofiq Habibulloh; Rosita Dewati; Muhammad Fathul Anwar (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2025)
Competition in processed food products, particularly packaged spice seasonings, has intensified alongside increasing consumer demand for practical, safe, and high-quality products. In relatively homogeneous markets, product attributes play an important role in influencing consumer purchasing decisions. This study aims to analyze the effect of product attributes on purchasing decisions for Ladaku Pepper Powder in Surakarta City. The product attributes examined include product quality, price, brand, packaging, quality assurance, and halal assurance. The study was conducted purposively in Surakarta City using a non-probability sampling technique with an accidental sampling approach. A total of 100 respondents were involved, meeting the following criteria: a minimum age of 17 years, having purchased Ladaku Pepper Powder at least twice, and residing in Surakarta City. The data were analyzed using multiple linear regression analysis. The results indicate that all product attributes have a significant effect on purchasing decisions for Ladaku Pepper Powder simultaneously. Partially, product quality, brand, quality assurance, and halal assurance have a positive and significant effect on purchasing decisions, while price and packaging do not have a significant effect. Product quality is identified as the most dominant attribute influencing purchasing decisions.